On the Buckling Response of Functionally Graded Carbon Nanotube-reinforced Composite Imperfect Beams - Boutaleb, Sabrina; Boulal, Ammar; Zidour, Mohamed; Al-Osta, Mohammed A.; Tounsi, Abdelouahed; Tounsi, Abdeldjebbar; Salem, Mohamed Abdelaziz; Khedher, Khaled Mohamed (Periodica Polytechnica Civil Engineering, 2024)
The current inquiry aims to scrutinize the porosity’s effect on the buckling response of carbon nanotube reinforced composite (CNTRC) imperfect beams. The developed theories account for higher-order variation of transverse shear strain through the depth of the beam and satisfy the stress-free boundary conditions on the top and bottom surfaces of the beam. Single-walled carbon nanotubes (SWCNTs) are distributed and aligned in a polymeric matrix with various reinforcement patterns to create CNTRC porous beams. The material properties of the functionally graded beam determined using the mixture rule are assumed to vary according to the power law distribution of the volume fraction of the constituents. The mathematical models presented in this study are validated through numerical comparison with existing results. The new buckling results of carbon nanotube-reinforced porous beams are analyzed considering the influence of several parameters, including volume fraction, aspect ratios, degree of porosity, and types of reinforcement. The results stipulate that the above parameters play a significant role in the critical buckling load variation. It is proclaimed that the critical buckling load dwindled as porosity increased and that the X-CNT reinforced beam has a high resistance against buckling compared to other reinforcement types.